Death when providing anesthesia in dentistry - Falcón-Guerrero , Britto Ebert (2023)
During the management of the patients who come to dental treatment, there are often situations that can be contributing to make some type of mistake or cause complications that go hand in hand, not only with the fact of a lack of capacity or preparation of the dentist, but the degree of collaboration or anxiety that the patient may have during their care; This level of collaboration is usually given by the good or bad experiences that the patient has previously had, which can cause fear and fear of being in front of dental treatment. Deaths rarely occur in doctors' offices and the implications for dentists can be deduced from scientific publications and internet reports on deaths in dental offices. This type of situation can result in a distraction or lack of vigilance of the professional before the procedure that is being performed. To establish death care, a review of the most recent articles in PubMed, Medline, and Cochrane is made.